I love you... I love you not A study on the reasons and patterns of romantic relationships among high school students. - Cargando, Sidney Pauline L., et al; Seneca, Mary Grace A. (Sidney Pauline L. Cargando, 2011)
The concept of romantic relationships among the youth today apparently differs from that of the previous generations'. The researchers were interested in the identification of the reasons for engaging in romantic relationships and patterns of romantic relationships. The study was conducted in the Leyte National High School campus, Tacloban City where of 1328 students as research respondents, 585 were identified to have had already engaged in romantic relationships. There were results from the 9-item questionnaire showed the top reason for engaging in a romantic relationship as "they love the person" (292 or 28.40%) while "misunderstanding" (243 or 22.21%) ranked first for the causes of breakups. "Texting" (286 or 26.79%) was the widely used courting strategy. It was found that in a span of one year, the respondents had engaged in romantic relationships more than thrice and the average lengths of these relationships were 1-5 months only. On the average, it also took 1-5 months before they engage in a new romantic relationship. The researchers concluded that the concept of love and relationships in general seemed to be misunderstood by adolescents.